'Jewish sectarianism' and the State of Israel. Issue 4 (1st October 2016) - Mathie, Nicola
ABSTRACT: As a term which is growing in use to categorise and describe tensions and conflicts within states and societies but which receives little analysis of its meaning, this article seeks to open-up the term 'sectarianism' and identify main components. Stimulated by rhetoric, actions and tensions within Israel, we will assess if 'sectarianism' is an important and useful term/concept to be applied in inter-/intra-Jewish tensions and how Jewish religious groups interact with the State of Israel and society. It will also assess how cases within Judaism and Israel serve to add understandings to discussions on 'sectarianism, ' particularly focussing upon 'sectarianism' within Jewish Ultra-Orthodox (Haredi) communities. The article will place a strong focus upon contemporary case studies and will assess the significance of language and how sectarianism is connected with extremism, violences and questions of power and (in)security. Through identifying main components and features within 'sectarianism' and through focussing on case studies, the article will observe how sectarianism contains deeper aspects – metaphysical, religious, ontological, existential, political and societal, a recognition which I argue is important for deepening understandings.